Anti-inflammatory flavagline glycosides and putrescine bisamides from Aglaia perviridis leaves. Issue 25 (19th June 2020) - An, Fa-Liang; Xu, Wen-Jun; Yang, Ming-Hua; Luo, Jun; Kong, Ling-Yi
Abstract : Four new cyclopenta[ b ]benzopyran glycosides (1 –4 ), aglapervirisins J-M, two new putrescine bisamides (6 –7 ), aglaiamides M − N, and a pair of novel flavagline enantiomer (±) aglapernin (8 ) were isolated from the leaves of A. perviridis . Their structures were elucidated based on comprehensive analysis of spectroscopic methods. The anti-inflammatory activities of those compounds were evaluated as inhibitory activities against lipopolysaccharide (LPS) induced nitric oxide (NO) production in RAW264.7 cell lines. Cyclopenta[ b ]benzopyran glycosides (1 –4 ) showed weak nitric oxide inhibitory activity with IC50 values ranging from 29.5 to 43.6 μM, and the putrescine bisamides (5 –7 ) exhibited potent nitric oxide inhibitory activity with IC50 values ranging from 7.4 to 19.5 μM. Graphical abstract: Image 1 Highlights: Four new cyclopenta[ b ]benzopyran glycosides and a pair of novel flavagline enantiomer were isolated from the leaves of A. perviridis. 1 was a rare cyclopenta[b]benzopyran possessing a putrescinyl benzoyl motif and a glucose moiety as well. Cyclopenta[ b ]benzopyran glycosides and the putrescine bisamides showed weak nitric oxide inhibitory activity in LPS-induced in RAW264.7 cell lines.